A phantom for 2D dose measurements in the vicinity of metal implants for photon and proton beams - Lechner, Wolfgang; Knäusl, Barbara; Brunner, Jacob; Georg, Dietmar; Kuess, Peter (Frontiers in Physics, 2024)
This work aimed to characterize a dedicated phantom for assessing the dose near metal implants for radiotherapy with photons and protons. A dosimetry audit phantom was redesigned to position a Gafchromic EBT-3 film within a bisected titanium pedicle screw (6.5 mm diameter). The mass density and the water equivalent thickness (WET) of the phantom material were determined. The phantom was irradiated using a photon arc and a horizontal proton beam in combination with a couch rotation of 20°, with three repeated measurements each. Treatment plans utilizing a single field covering the screw and the EBT-3 film were optimized to deliver a physical dose of 2 Gy using a collapsed cone and Monte Carlo dose engine for photons and protons, respectively. The mass density and the WET of the phantom were determined as (1.033 ± 0.010) g cm−3 and (1.022 ± 0.013), respectively. Ionisation chamber measurements agreed within 1 % (photons) and 0.5 % (protons) with the calculated dose values. Relative photon dosimetry measurements using EBT-3 films revealed an agreement between measured and calculated horizontal profiles within the confidence interval for areas beyond 5 mm from the center. For photon plans, significant deviations of more than 10 % were found at the interfaces between phantom material and screw. The proton measurements showed a gradual decrease of 3 % across both profiles. In contrast to photon plans, no dose increase was measured within the screw, but significant dose fluctuations (>5 %) in the beam’s exit region. This study showed that the behavior of dose engine is affected by metal implants and thus dosimetric measurements are highly recommended. The presented phantom can serve as foundation for dedicated end-2-end phantoms.